2016
DOI: 10.1186/s40409-016-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Melittin induces in vitro death of Leishmania (Leishmania) infantum by triggering the cellular innate immune response

Abstract: BackgroundApis mellifera venom, which has already been recommended as an alternative anti-inflammatory treatment, may be also considered an important source of candidate molecules for biotechnological and biomedical uses, such as the treatment of parasitic diseases.MethodsAfricanized honeybee venom from Apis mellifera was fractionated by RP-C18-HPLC and the obtained melittin was incubated with promastigotes and intracellular amastigotes of Leishmania (L.) infantum. Cytotoxicity to mice peritoneal macrophages w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
1
29
0
1
Order By: Relevance
“…The two major reactive species in macrophages are superoxide (O 2 − ) and nitric oxide (NO) [37,38]. It is observed that if drugs have ideal anti-parasitic effects, the NO and H 2 O 2 productions of leishmania-infected macrophages decrease [4,39]. In our research, elevated levels of NO and H 2 O 2 were found in leishmaniainfected macrophages and a strong inhibition of NO and H 2 O 2 metabolites was observed upon treatment with DHCsA-d or SSG.…”
Section: Discussionmentioning
confidence: 99%
“…The two major reactive species in macrophages are superoxide (O 2 − ) and nitric oxide (NO) [37,38]. It is observed that if drugs have ideal anti-parasitic effects, the NO and H 2 O 2 productions of leishmania-infected macrophages decrease [4,39]. In our research, elevated levels of NO and H 2 O 2 were found in leishmaniainfected macrophages and a strong inhibition of NO and H 2 O 2 metabolites was observed upon treatment with DHCsA-d or SSG.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, melittin from Apis mellifera acted in vitro against promastigotes and intracellular amastigotes of Leishmania infantum. The results suggested that melittin can indirectly eliminate the parasite through a macrophage immunomodulatory effect [61]. Bee venom is also known to exhibit antifungal activities.…”
Section: Antimicrobial Agents From Wasps and Beesmentioning
confidence: 99%
“…Even as singular or a hybrid peptide, it was studied against Leishmania spp. and Trypanosoma spp., and researchers found direct antimicrobial and indirect immunomodulatory results [27][28][29][30].Another promising result was found about HIV. Dosedependently, melittin was found to prevent synthesis of group-specific antigen (gag)/DNA polymerase (pol) and intracellularly reduce Gag antigen and HIV-1 mRNA levels.…”
Section: Major Bioactive Substancesmentioning
confidence: 99%